A longitudinal analysis of urological chronic pelvic pain syndrome flares in the Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network. (29th May 2019) - Sutcliffe, Siobhan; Gallop, Robert; Henry Lai, Hing Hung; Andriole, Gerald L.; Bradley, Catherine S.; Chelimsky, Gisela; Chelimsky, Thomas; Quentin Clemens, James; Colditz, Graham A.; Erickson, Bradley; Griffith, James W.; Kim, Jayoung; et al.
Abstract : Objective: To describe the frequency, intensity and duration of urological chronic pelvic pain syndrome symptom exacerbations ('flares'), as well as risk factors for these features, in the Multidisciplinary Approach to the Study of Chronic Pelvic Pain Epidemiology and Phenotyping longitudinal study. Participants and Methods: Current flare status ('urological or pelvic pain symptoms that are much worse than usual') was ascertained at each bi‐weekly assessment. Flare characteristics, including start date, and current intensity of pelvic pain, urgency and frequency (scales of 0–10), were assessed for participants' first three flares and at three randomly selected times when they did not report a flare. Generalized linear and mixed effects models were used to investigate flare risk factors. Results: Of the 385 eligible participants, 24.2% reported no flares, 22.9% reported one flare, 28.3% reported 2–3 flares, and 24.6% reported ≥4 flares, up to a maximum of 18 during the 11‐month follow‐up (median incidence rate = 0.13/bi‐weekly assessment, range = 0.00–1.00). Pelvic pain (mean = 2.63‐point increase) and urological symptoms (mean = 1.72) were both significantly worse during most flares (60.6%), with considerable within‐participant variability (26.2–37.8%). Flare duration varied from 1 to 150 days (94.3% within‐participant variability). In adjusted analyses, flares were more common, symptomatic, and/or longer‐lasting in women and in those with worse non‐flare symptoms, bladder hypersensitivity, and chronic overlapping pain conditions. Conclusion: In this foundational flare study, we found that pelvic pain and urological symptom flares were common, but variable in frequency and manifestation. We also identified subgroups of participants with more frequent, symptomatic, and/or longer‐lasting flares for targeted flare management/prevention and further study.